2005
DOI: 10.1016/j.ejheart.2005.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Reversible ventricular dysfunction takotsubo cardiomyopathy

Abstract: Background: Recently, many cardiologists have recognized the existence of a rapidly reversible form of heart failure of unknown origin characterized by a takotsubo-shaped, dyskinetic left ventricle on left ventriculography. Aim: To determine the detailed clinical features of takotsubo cardiomyopathy. Methods: Thirteen elderly patients (11 women and 2 men with a mean age of 75.3 years) who had normal coronary arteries and takotsubolike left ventricular dysfunction were prospectively enrolled in this study. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(21 citation statements)
references
References 34 publications
1
19
1
Order By: Relevance
“…We propose that low SVR may be either a compensatory mechanism operating to maintain normal cardiac output under resting conditions and/or an integral part of the SIC pathophysiology. In a previous study, it has been reported that cardiac output is decreased during the acute stage of SIC [29]. The reason for the discrepancy between our findings may be due to patient selection, different diagnostic criteria for SIC used and different timing of hemodynamic evaluation.…”
Section: Discussioncontrasting
confidence: 76%
“…We propose that low SVR may be either a compensatory mechanism operating to maintain normal cardiac output under resting conditions and/or an integral part of the SIC pathophysiology. In a previous study, it has been reported that cardiac output is decreased during the acute stage of SIC [29]. The reason for the discrepancy between our findings may be due to patient selection, different diagnostic criteria for SIC used and different timing of hemodynamic evaluation.…”
Section: Discussioncontrasting
confidence: 76%
“…However, elevated catecholamine levels are not uniformly found in patients with this syndrome. 3 High plasma catecholamine levels in patients with pheochromocytoma are well known to induce reversible cardiomyopathy. 20 …”
Section: Concepts About Pathophysiologymentioning
confidence: 99%
“…It is important to pay attention to the hemodynamics in the acute phase, which often correspond to New York Heart Association class III heart failure. 3 Only a handful of recurrent takotsubo cardiomyopathy cases have been reported. Mechanisms underlying susceptibility to recurrence are not understood.…”
Section: Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…Intra-aortic balloon pump can be used to support the haemodynamic state in cardiogenic shock with or without LVOT obstruction. 63 The use of catecholamines as intotropic agents should be considered carefully in this situation, since catecholamines excess may play an important role in this condition and LVOT obstruction can be worsened. Levosimedan has been suggested, 64,65 although clinical data are limited to date.…”
Section: Treatmentmentioning
confidence: 99%